Československá sociologická společnost při ČSAV v zrcadle svých Zpráv (1964–69).: (K 60. výročí České sociologické společnosti) - Nešpor, Zdeněk R. (Lidé města, 2024)
The Czechoslovak Sociological Society, which was founded sixty years ago in 1964, was an important player in the re-establishment of Czech (Czechoslovak) sociology in that era. The society gradually took over the academic management of the field and its international representation, commencing the application of democratic and meritocratic principles. Through its activities, it became both a pioneer and a witness of the Prague Spring. However, these efforts were ended after the violent suppression of the Prague Spring, at the latest in the early 1970s. While the history of the beginnings of the Czechoslovak Sociological Society has already been covered elsewhere, in this article, the author analyses its reflection by the internal bulletin/journal entitled Zprávy ČSSS (Reports of the CSSS), published in 1965–69. Although he admits the significant openness of the periodical, he also shows its limits and the fact that even during the Prague Spring, the management and everyday life of Czech academia was not fully transparent.